EKSPLORASI PERAN KEPEMIMPINAN DALAM MENGEMBANGKAN ETOS KERJA DAN KINERJA KARYAWAN PADA PT WALLETKU INDOMPET INDONESIA TEBET JAKARTA SELATAN - Rahim Silalahi, Abdul; Yanuarti, Maghfiroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify the leadership style at PT Walletku Indompet Indonesia, the work ethic demonstrated by employees, the level of employee performance, and the role of leadership in developing work ethic and enhancing employee performance. This research employs a descriptive qualitative method, with observation, interviews, and documentation as data collection techniques. The subjects of the study include leaders and employees from various divisions within PT Walletku Indompet Indonesia. The findings indicate that the leadership style applied tends to be participative and open, with leaders actively involved in field observations and engaging employees in decision-making processes. This leadership approach is considered communicative and supportive, although it is not yet balanced with an adequate reward system, which affects employees' emotional motivation. Employees generally display a positive work ethic, characterized by discipline, hard work, and a strong sense of responsibility, although there is a risk of burnout due to high performance targets and flexible working hours. Employee performance is generally classified as good, as evidenced by the achievement of targets and timely task completion, although there are still communication and coordination barriers between divisions and technical issues that hinder team effectiveness. The findings also show that communicative and supportive leadership plays a significant role in shaping a positive work ethic and encouraging improved performance. support sustainable development, it is recommended to strengthen the appreciation and reward system, implement consistent internal supervision, and provide adaptive training related to technology and modern work systems